Factors Associated With Alzheimer’s Disease Patients’ Caregiving Status and Family Caregiving Burden in China - Li, Yuxian; Leng, Fangda; Xiong, Qi; Zhou, Jiong; Du, Ailian; Zhu, Feiqi; Kou, Xiaowen; Sun, Wei; Chen, Luzeng; Wang, Huali; Xie, Hengge; Gao, Feng; et al. (Frontiers in Aging Neuroscience, 2022)
Background: The increasing prevalence of Alzheimer's disease (AD) has emerged as a major challenge worldwide. China as the most populous country in the globe is amid rapid aging of its population, highlighting the need for appropriate social and medical policies to meet the challenge. The current study aims to provide understanding of the current status of caring given to AD patients in China and the underlying factors with a large multicenter cross-sectional observational approach. Methods: A total of 1675 patients with probable AD from 30 provincial regions of mainland China were enrolled in the current study from August 2019 to December 2019. We analyzed the caregiving status and its relationship with family burden and various socioeconomical and medical factors. Results: 90.87% of the patients enrolled adopted family care. The choice of caregiving method was influenced by factors including age (>80 years old, OR 0.648; 95% CI, 0.427–0.983) , overall family burden (high, OR 0.574; 95% CI, 0.0.373–0.884) , patients’ income (OR 0.511; 95% CI, 0.330–0.789) and self-care ability (OR 0.329; 95% CI, 0.183–0.588). Conclusion: Family care is the primary method of care for AD patients in China and the institutional care system for AD patients is still underprepared in China.